Vpliv vode, piridina in dioksana na celulozo - Tišler, Vesna (Les (Ljubljana), 2002)
At reviewing the literature it was established that water, pyridine and dioxane have different effects on cellulose. Water causes swelling of cellulose. Pyridine adsorbes on cellulose, but it`s swelling effect is lesser than at water. Dioxane can not form hydrogene bonds. For that reason it can not adsorbe on cellulose, it may incorporates itself into cellulose`s structure.
Keywords: celuloza; voda; piridin; dioksan